Recovery of Catalyst from Tar Formed in Phenol Production Unit - T. Mohammed, Wadood; M. Zaboon, Sami (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
This work was conducted to study the recovery of catalyst and desirable components from tar formed in phenol production unit and more particularly relates to such a method whereby better recovery of copper salts, phenol, benzoic acid and benzoate salts from tar by aqueous acid solution was accomplished. The effect of solvent type, solvent concentration (5, 10, 15, 20, 25 and 30 wt%), agitation speed (100, 200, 300 and 400 rpm), agitation time (5, 10, 15, 20 and 25 min), temperature (90, 100, 110, 120, 130 and 140 oC) , phase ratio (1/1, 2/1, 3/1, 4/1 and 5/1) and number of extraction (1, 2, 3, 4, and 5) were examined in order to increase the catalyst and desirable components extraction. Four types of solvent were used; hydrochloric acid, acetic acid, propanoic acid and butanoic acid with different concentration. The results of this work exhibit that the highest removal of copper 80.2 wt%, phenol 89.1 wt%, benzoic acid 90.7 wt% and benzoate salts 87.3 wt% were obtained under the conditions of Acetic acid-water of 15%, Agitation speed = 300 rpm, Agitation time = 20 min, Temperature = 120C, Phase ratio (A/O) = 4 / 1, and Number of extraction cycle = 4.